Ecology and silviculture of silver fir (Abies alba Mill.): a review - Dobrowolska, Dorota; Bončina, Andrej; Klumpp, Raphael (Journal of forest research, 2017)
Silver fir (Abies alba Mill.) is one of the most valuable conifer trees in Europe for historical and economic reasons. Growing interest in the species, along with the recognition that silver fir was subjected to inappropriate silvicultural measures during the 20th century due a lack of understanding of its ecology, have spurred recent studies from various disciplines which have yielded new insights into the gene ecology, history, ecology, structure and dynamics of fir populations. In this paper, we provide a multidisciplinary, synoptical review discussing the prospects for silver fir forestry in the 21st century. We describe the main characteristics of the history and ecology of silver fir, with a particular emphasis on gene ecology and the structure and dynamics of fir populations with respect to mixed stands and fir management. Fir is a fundamental species for maintaining high biodiversity in forested ecosystems because of its shade tolerance, plasticity to environmental conditions and ability to coexist with many tree species. Silver fir ecotypes show remarkable variation in features such as frost hardiness, drought resilience and shade tolerance. Fir can create stands of heterogeneous stand structure, from one-storied through to multi-storied structure and finally to selection structure. Natural regeneration of fir will be scarce if fir stands are managed inappropriately through the application of clear cutting, a short regeneration period and abrupt removal of shelter trees. Climate change is expected to reduce the abundance and distribution range of silver fir. Improvements in forest management treatments are recommended to improve silver fir conservation.